Reinforce Nationality Through Religious Local Tradition (Case Study of Malam Tirakatan in Yogyakarta) - Wildan Imaduddin Muhammad (IBDA` : Jurnal Kajian Islam dan Budaya, 2016)
Celebrating of IndependenceDay became a part of symbol of honour from the citizenship for their country. In many places freedom is celebrated, including in Indonesia. The celebration is an annual event organized by goverment and citizen, both formal and informal. Formally, the goverment of Indonesia from local level to the centre celebrate this day by flag ceremony on the seventeent of August. Somehow in non-formal, citizen commemorate this day by various manner such aspanjatpinang contest etc. One form of celebration in Indonesia to celebrate the independence day is called â€œmalam tirakatanâ€ or â€œmalam pitulasanâ€, especially in the area of Yogyakarta. Malam tirakatan is kind of acculturation from Moslem local tradition.This paper describe aboutmalam tirakatanas an acculturation between religious local traditions with a sense of nationalism. I use the method of triangulation for collect data which are participant observation, deep interview and documentation. The location of this research is focused on two different places, first in Dukuh the village of Bantul district and second in Ngaseman village, a part of village of Kulon Progo district. From this research known that Indonesian Moslems reinforce their nationality by their religious local tradition.